Interrogating Identity and Nationalism in Khushwant Singh's Fiction with Special Reference to A Train to Pakistan (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Khushwant Singh's literary oeuvre has long been celebrated for its nuanced exploration of the complexities and contradictions inherent in the Indian nationalist project. This research paper focuses on the author's seminal novel A Train to Pakistan, examining how Singh's fiction interrogates the notions of identity, community, and nationalism in the context of the Partition of India. Drawing on postcolonial and nationalist theories, the study analyses the ways in which the novel challenges simplistic binaries of "us" and "them," instead presenting a multifaceted portrayal of the human experience amidst the violence and upheaval of Partition. The paper argues that through the distinctive characterizations and narrative techniques employed in A Train to Pakistan, Khushwant Singh offers a powerful counterpoint to the reductive and often exclusionary discourses that have historically dominated the discourse on Indian nationalism. By foregrounding the personal stories and lived realities of individuals caught in the throes of this transformative historical moment, the author's fiction serves to humanize and complexify the nationalist project, inviting readers to engage with the nuances and ambiguities that have shaped the postcolonial condition in India. This study ultimately positions Khushwant Singh as a vital literary voice whose work continues to resonate with scholars and readers alike, contributing to a more nuanced understanding of the intersections between identity, community, and the politics of nation-building.